Prevention and control of infectious disease transmission in subways: an improved susceptible–exposed–infected–recovered model - Fang Zhou; Fang Hou; Jiangtao Wang; Qiaoyun Ma; Lanfen Luo (Frontiers in Public Health)
IntroductionA well-connected transportation network unites localities but also accelerates the transmission of infectious diseases. Subways—an important aspect of daily travel in big cities—are high-risk sites for the transmission of urban epidemics. Intensive research examining the transmission mechanisms of infectious diseases in subways is necessary to ascertain the risk of disease transmission encountered by commuters.MethodsIn this study, we improve the susceptible–exposed–infected–recovered (SEIR) model and propose the susceptible–exposed–infected–asymptomatic infected (SEIA) model. First, we added asymptomatic patients to the improved model as a parameter to explore the role of asymptomatic patients in the transmission of infectious diseases in a subway. The numbers of boarding and alighting passengers were added to the model as two time-varying parameters to simulate the exchange of passengers at each station.ResultsThe improved model could simulate the transmission of infectious diseases in subways and identify the key factors of transmission. We then produced an example of the transmission of coronavirus disease (COVID-19) in a subway using real subway passenger data substituted into the model for the calculations.DiscussionWe ascertained that the number of exposed people continuously increased with the operation of the subway. Asymptomatic patients had a greater impact on the transmission of infectious diseases than infected people in the course of transmission. The SEIA model constructed in this study accurately determined the spread of infectious diseases in a subway and may also be applicable to studies on the transmission of infectious diseases in other urban public transport systems.